1979
DOI: 10.1099/0022-1317-43-1-151
|View full text |Cite
|
Sign up to set email alerts
|

The Polypeptide and the DNA Restriction Enzyme Profiles of Spontaneous Isolates of Herpes Simplex Virus Type 1 from Explants of Human Trigeminal, Superior Cervical and Vagus Ganglia

Abstract: SUMMARYAnalysis of the infected cell polypeptides and the DNA restriction profiles of 3 I HSV-I isolates from the trigeminal, superior cervical and vagus ganglia from I7 individuals (52 U.S.A., 2 Japanese, 3 Norwegian) could be classified as 15 different virus strains. With the exception of the three Norwegian isolates which gave identical profiles, virus isolates from the ganglia of different individuals could all be distinguished from one another. In contrast virus isolates from the trigeminal, superior cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

1981
1981
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 0 publications
3
50
1
Order By: Relevance
“…However, it may be argued that a successful superinfection of latently infected ganglionic cells should not normally occur since previous studies have indicated that the first virus inoculated, colonizing the ganglion, would prevent a subsequently added virus strain from entering it (Price eta[., 1975;McKendall, 1977;Centifanto-Fitzgerald et al, 1982). The existence of such an impediment to superinfection is also supported by findings that each attempt to recover virus from explanted, latently infected human ganglia has yielded a single virus strain only (Lonsdale et at., 1979). On the other hand, Meigner et al (1983) recently reported colonization of mouse ganglia with several, subsequentiaUy inoculated HSV strains.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, it may be argued that a successful superinfection of latently infected ganglionic cells should not normally occur since previous studies have indicated that the first virus inoculated, colonizing the ganglion, would prevent a subsequently added virus strain from entering it (Price eta[., 1975;McKendall, 1977;Centifanto-Fitzgerald et al, 1982). The existence of such an impediment to superinfection is also supported by findings that each attempt to recover virus from explanted, latently infected human ganglia has yielded a single virus strain only (Lonsdale et at., 1979). On the other hand, Meigner et al (1983) recently reported colonization of mouse ganglia with several, subsequentiaUy inoculated HSV strains.…”
Section: Introductionmentioning
confidence: 58%
“…1 x 108 cells) were infected with 0.1 p.f.u, of HSV per cell in 10 ml of medium at 37 °C for 1 h. Eagle's MEM (20 ml) was then added to each bottle, which was incubated at 37 °C for 48 h. The infected cells were scraped off with a rubber policeman, washed twice in phosphate-buffered saline (PBS), and then collected by low-speed centrifugation (800 g for 10 min at 4 °C). HSV DNA was extracted by a modification of methods described previously (Green et al, 1971 ;Buchman et aL, 1978 ;Lonsdale et al, 1979 ;Pignani et al, 1979). Five ml of lysing solution (0.25 ~ Triton X-100, 10 mM-EDTA, 10 mM-Tris HC1 pH 7.9) was added to the infected cells.…”
Section: Methodsmentioning
confidence: 99%
“…Our observations raise the question why all field isolates examined to date are diploid for repetitive sequences (Hayward et al, 1975 a;Skare et al, 1975;Lonsdale et al, 1979). We can envisage several explanations.…”
Section: Expression Of Hsv Long Repetitions 189 Discussionmentioning
confidence: 95%
“…The analysis of herpes simplex virus (HSV) strains by restriction endonuclease (RE) cleavage sites has been used not only to distinguish between HSV types 1 and 2 but also for strain differentiation within an HSV type (Roizman, 1979(Roizman, , 1980Lonsdale et al, 1979Lonsdale et al, , 1980Maitland et al, 1982;Ueno et al, 1982;Umene et al, 1984;Sakaoka et al, 1987 a, b;Umene & Yoshida, 1989;Umene & Sakaoka, 1991). The existence of intratypic polymorphism in HSV genomes led to the establishment of a new field in terms of molecular epidemiology (Roizman & Buchman, 1979;Buchman et al, 1980;Roizman & Tognon, 1983;Sakaoka et al, 1984Sakaoka et al, , 1985.…”
Section: Introductionmentioning
confidence: 99%